An in vitro system from Plasmodium falciparum active in endogenous mRNA translation - Ferreras Ana; Triana Ledia; Correia Heriberto; Sánchez Erlinda; Herrera Flor (Memorias do Instituto Oswaldo Cruz, 2000)
An in vitro translation system has been prepared from Plasmodium falciparum by saponin lysis of infected-erythrocytes to free parasites which were homogeneized with glass beads, centrifuged to obtain a S-30 fraction followed by Sephadex G-25 gel filtration. This treatment produced a system with very low contamination of host proteins (<1%). The system, optimized for Mg2+ and K+, translates endogenous mRNA and is active for 80 min which suggests that their protein factors and mRNA are quite stable.